Artificial Intelligence-Enhanced Transformational Leadership and Organizational Learning in Healthcare Organizations: A Review from Management and Organization Theories - Ufuk Burak Karcıoğlu (Middle Black Sea Journal of Health Science, 2026)
Background: Artificial intelligence (AI) is increasingly transforming healthcare management by enhancing decision-making, leadership practices, and organizational learning processes. Despite the growing adoption of AI technologies in healthcare organizations, their integration with established management and organization theories, particularly transformational leadership.Review Text: This narrative review synthesizes the literature on AI-enhanced transformational leadership and organizational learning in healthcare organizations. Drawing on the foundational theories, the review examines how AI technologies, including predictive analytics and machine learning, support the four dimensions of transformational leadership: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The review further explores how AI accelerates organizational learning through single-loop and double-loop learning processes by facilitating knowledge generation, dissemination, and evidence-based decision-making. Case examples are discussed to illustrate AI’s role in improving clinical decision support, operational efficiency, and organizational knowledge management.Conclusion: AI has significant potential to strengthen transformational leadership and organizational learning in healthcare organizations by enabling data-driven innovation, personalized leadership approaches. This review contributes to the healthcare management literature by linking AI applications with established management theories and provides directions for future research on the long-term organizational impacts of AI in diverse healthcare settings.